Kat Adetleri Farklı Betonarme Binaların Doğrusal Olmayan Analiz Yöntemleriyle İrdelenmesi - Moral, Abdurrahman (Fen Bilimleri Enstitüsü, 2014)
Son yirmi yıl içinde dünyada meydana gelen büyük depremlerden alınan dersler sonucunda, yeni inşa edilecek binaların depreme dayanıklı tasarımı, mevcut binalarda deprem etkisinde oluşması beklenen hasar mertebesinin belirlenmesi ve deprem güvenliği yetersiz binalarda uygulanacak güçlendirme tekniklerinin neler olması gerektiği ile ilgili konular yeniden gözden geçirilmiştir. Bu çalışmaların sonucu olarak performansa dayalı tasarım ve değerlendirmeyi esas alan bir çalışma alanı doğmuş ve hızla gelişmeye başlamıştır. DBYBHY 2007 de yeni yapılacak binalar için bir hesap esasları ve mevcut binaların deprem davranışlarının değerlendirilmesi için ise, doğrusal olan ve doğrusal olmayan değerlendirme yöntemleri bulunmaktadır. Mevcut binaların değerlendirilmesinde kullanılan yöntemlerin birbiri ile uyuşumu ve bunların her ikisinin yeni bina tasarımında kullanılan yöntemle uyuşumu, DBYBHY 2007’nin uygulanmasında önemli bir hususu oluşturmaktadır. Bu çalışmada DBYBHY 2007 Bölüm 2 ve 3’e göre yeni olarak tasarlanan binaların, mevcut bina kabul ederek DBYBHY 2007 de mevcut binalar için tanımlanan performans hedefleri, kat parametresinin etkisi ve sonuçlar arasındaki uyuşum üzerinde durulmuştur. Bu çalışmada DBYBHY 2007‘e göre tasarımı yeni ofis binası olarak tasarlanmış 3 katlı, 5 katlı ve 7 katlı olmak üzere seçilen üç bina esas alınarak, yeni tasarımın beklenen performans hedefini sağlama durumu ve bina kat adedinin bina performans hedefi üzerine olan etkisi ve Artımsal Eşdeğer Deprem Yükü Yöntemi ile Zaman Tanım Alanında Doğrusal Olmayan Analiz Yöntemlerinin birbirleri ile uyuşumu söz konusu edilmiştir. Bu binaların deprem yükleri altındaki taşıyıcı sistem performanslarını belirleyebilmek için yönetmelikte bulunan doğrusal olmayan çözüm yöntemleri kullanılmıştır. Doğrusal olmayan çözümde Artımsal Eşdeğer Deprem Yükü Yöntemi ile Zaman Tanım Alanında Hesap Yöntemi seçilmiştir. DBYBHY 2007’e göre tasarımı yapılan bu binaların sağladıkları performans hedefleri aralarında ve birbirleriyle karşılaştırılmıştır. Ayrıca, bu karşılaştırmada binaların sağladıkları performans hedefleri kat adedinin farklı olması açısından da değerlendirilmiştir.

During the past two decades, many large-scale earthquakes have occurred consecutively around the world. These earthquakes resulted in hundreds of thousands of casualties and in significant economic damage. Based on the lessons learned fromthe earthquakes, seismic codes need to be upgraded. In the upgrading of the seismiccodes, there are some topics as follows: i) earthquake-resistant design of new reinforced concrete (RC) structures ii) evaluation of existing RC structures iii) developing new strengthening techniques for existing RC structures with insufficient earthquake resistance. For this purpose, performance based design and seismic evaluation techniques of existing RC structures become urgent thus they have been developed rapidly. In the present days, many linear or nonlinear analysis methods are available for the performance based design and seismic evaluation of the existing structures. Since material and geometric nonlinearity are not considered in the linear analysis methods, these methods are easy to employ in the seismic evaluation of the structures but their results are not so reliable. There are two types of nonlinear analysis methods which are known as nonlinear static and dynamic analysis. The more realistic results can be obtained by employing the nonlinear static analysis methods if they are compared with linear analyses ones. On the other hand, nonlinear dynamic analysis method is the advanced method since it can be possible to monitor the real behaviour of the structures during earthquakes. The codes of earthquake is the most significant resource that can be used to build an earthquake – resistant building. According to their geographical location, their geological and sesimic characteristics that apply within the territory and local ground conditions, countries prepare regulations that includes the rules which must be followed during building design. For this purpose, The Ministry of Public works and settlement in Turkey prepare The Regulations of Buildings that will be built in Seismic Zone 2007. Seismic loads generate the most inconvenient internal forces of the structural elements. There are different methods of calculating the force of earthquakes affecting on buildings. These are called seismic load calculation methods. After determining the essential one of the methods for our system, the force of earthquakes and its distribution over structural elements must be calculated in the way the chosen method requires. Determining the suitable methods for structures are given in Turkish Earthquake Code 2007 (TEC2007) . Three alternative seismic load calculation methods are presented by the seismic code. “Equivalent Seismic Load Method”, “Modal Superposition Method”, and Time Increment Methods” are indicated for seismic load calculations in our seismic code. Equivalent Seismic Load Method is a widespread seismic load calculation method and it can be found in many seismic codes in the world. In Mode Superposition Method, the maximum internal forces and displacements are obtained by the calculation of the maximum contributions of each adequate vibration modes that combined statisticly. In Tıme Increment Methods, in order to investigate the structural behavior of the building under seismic loading, an earthquake is assigned to the building as lateral load and the time history analysis is carried out. TEC2007 which establishes rules abouth buildings to be built in disaster areas includes chapter 2 and 3 where methods are given for reinforced concrete buildings to be designed. The Code also has a new chapter (Chapter 7) where the linear and the non-linear evaluation methods are given for seismic safety evaluation of existing buildings. Consistency between the results of the methods used for seismic evaluation of existing buildings is important for thecnical as well as legal decision. Also it is important to design a building according to the rules given for new buildings and later to consider the same building as an existing one and apply evaluation procedure and check whether it satisfies the performance goal designed for. The harmony of the results is also important for practical purposes. In this study, three RC buildings of 3, 5 and 7 stories are considered are designed in accordance with the provisions of TEC2007 and general requirements for design and construction of RC structures. Then, three buildings are assumed to be current buildings and are analyzed by employing the two nonlinear static analysis methods for existing buildings. These methods are Incremental Equivalent Earthquake Load Method which is an application of Static Pushover Analysis and Nonlinear Time History Analysis Method mentioned in TEC2007. The static pushover analysis is becoming a popular methods for seismic performance evaluation of existing and new structures. The expectation is that the pushover analysis will provide adequate information on seismic demands imposed by the design ground motion on the structural system. Time history analysis is another seismic calculation method for existing and new structures in our seismic code. The method makes use of earthquakes acceleration – time records that occured previously or similar artificial records which constituted. In the thesis, three earthquake records which will be used in time history analysis simulated to design spectrum as taking notice of related soil class. In present study, their performance are evaluated by considering the buildings as existing ones. It is expected that all of the buildings, which have been designed with linear elastic methods, achieve the Life Security performance level whose exceeding possibility is predicted for offices building as 10% in 50 years according to the Seismic Regulation. Besides Incremental Equivalent Earthquake Load Method and Nonlinear Time History Analysis Method results are compared. The results are given comparatively and is paid to the effect of the number of stories of the buildings on their performance goals. According to the study, in the performance evaluation which is the consequence of all buildings’s Incremental Equivalent Earthquake Load Method, it is observed that all buildings achieve the Life Security performance level whose exceeding possibility is predicted for residences as 10% in 50 years according to the TEC2007. And it is clearly seen that, The Nonlinear Time History Analysis Method results is reaching greater value than Incremental Equivalent Earthquake Load Method results in terms of base shear force and roof displacement. And It is observed that the biggest base shear force (time-dependent) and roof displacement value, which have been calculated in consequence of time history analysis, yield the most proximate results with pushover curves in 3 stories building. In the future it is expected that these methods would be also commonly used for new structure designs besides performance evaluation of existing structures. According to this fact the regulations would be improved. And for the improvement of these new regulations, it could be recommended that the damage limits to be determined not according to unit displacements occurred in concrete and steel, but according to directly plastic rotations occurred in section (as in FEMA 356). So that the analyses could be performed more practical and controlled.
An Investigation Of Rc Buildings Having Various Stories By Using Nonlinear Analysis
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2014
Thesis (M.Sc.) -- İstanbul Technical University, Instıtute of Science and Technology, 2014
Keywords: Performans Değerlendirmesi; Doğrusal Olmayan Deprem Davranış Değerlendirme Yöntemleri; Zaman Tanım Alanında Hesap Yöntemi; Seismic Performance Evaluation; Non-linear Seismic Evaluation Methods; Time History Analysis